Pembelajaran Seni Tari Pada Anak Tunarungu Di SLB ABCD Caringin (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Deafness is a condition in which someone experiences hearing disorders, which usually causes the individual to have special needs. Deafness is one form of diversity owned by our community, and it is not uncommon that the differences in diversity become something not acceptable so easily. This research was initiated to dive deeper into the proof that even with special needs, a deaf person could also grow to their potential, and one of the ways is through art, especially the art of dance. The method used in this study is descriptive qualitative research methods through observation and interview. Other than pursuing artwork, dancing also becomes a medium for deaf students to develop personality and motor skills. The teacher’s role is crucial, and it is well regarded that further there will be more creative ways to enrich arts pursued by people, and especially children or students with special needs.